Perception on work stressor and stress management : a case study at Sabah Royal Malaysian Custom Department (RMC) / Shahrul Azhar Sardilin - Sardilin, Shahrul Azhar (2011)
Recently job and workplace stress had attracted concern among the public, media, and especially among the employee (government servant and private sector). Workplace health and safety representative always try to identify why and caused the problem arise and try to find an alternative solution and control tools for this matters. Stress in workplace can influence the officer and the department entirely. Some of the stress may result in individual positively and negatively. Overall workplace climate must be supportive, workload must be delegate fairly, and transparency with the department policies to their officers and the most important thing is having a good relationship within or outside the department.